O controle da informação da vida: a propriedade intelectual do código genético - Humberto Alves de Vasconcelos Lima (2013)
This study aims at the analysis of intellectual property rights in the genetic code as well as the legal and economic implications that derive from it. These implications are related to the suitability of this type of intellectual property to the patentability criteria in a technical-legal aspect, and, from an economic perspective, to the practical consequences of the same nature that the exclusion prerogative determines. The research is based on the assumption that this type of intellectual property is not legitimate, either when examined under legal criteria, whether in the economic analysis. To test the hypothesis, propedeutical aspects of intellectual property are revisited, especially looking for a conceptual definition suited to the peculiarities of this form of property. Subsequently, it investigates how the information is legally controlled, especially in the context of international trade. In this issue, it analyzes patentability criteria as impacting gene patents, also investigating the propagation of the doctrine of natural extracts in the jurisprudence of the United States. The economic consequences which gene patents prerogative of exclusion and other DNA sequences causes, as well as the constraints that guide this exclusion are researched too. Finally, with regard to the rhetoric of justification, it analyzes the main theories offered to legitimize intellectual property, those of natural law and of utilitarian economic nature, for in the end find what theoretical framework best suits to DNA patents. In conclusion, the hypothesis is confirmed by demonstrating that the intellectual property of the genetic code is not juridical and economically legitimate.